What Do You Think Is New About CCAFS? - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Interview with Ashan Uddin Ahmed from Centre for Global Change, Bangladesh. Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya